New insights into the subterranean genus Speoplanes Müller, 1911 (Coleoptera, Leiodidae, Cholevinae) from the Dinarides - Mizerakis, Vangelis; Hlaváč, Peter; Čeplík, Dávid; Jalžić, Branko; Faille, Arnaud (Zootaxa, 2022)
In the present study morphological and molecular data from specimens of the troglobitic genus Speoplanes have been examined. The two subspecies Speoplanes giganteus giganteus Müller, 1911 and Speoplanes giganteus biocovensis Müller, 1934 are changed in rank from subspecies to species level and discrete identification characters for the separation of the two species are provided. Additionally, all known localities of the species (including new records) are listed and a distribution map of the genus is provided.